Anti‐CD19 and anti‐BCMA CAR T cell therapy followed by lenalidomide maintenance after autologous stem‐cell transplantation for high‐risk newly diagnosed multiple myeloma. Issue 5 (9th February 2022) - Shi, Xiaolan; Yan, Lingzhi; Shang, Jingjing; Kang, Liqing; Yan, Zhi; Jin, Song; Zhu, Mingqing; Chang, Huirong; Gong, Feiran; Zhou, Jiazi; Chen, Guanghua; Pan, Jinlan; et al.
Abstract: Few prospective studies have examined posttransplant chimeric antigen receptor (CAR) T cell infusion as candidates for front‐line consolidation therapy for high‐risk multiple myeloma (MM) patients. This single‐arm exploratory clinical trial is the first to evaluate the safety and efficacy of sequential anti‐CD19 and anti‐BCMA CAR‐T cell infusion, followed by lenalidomide maintenance after autologous stem cell transplantation (ASCT), in 10 high‐risk newly diagnosed multiple myeloma (NDMM) patients. The treatment was generally well tolerated, with hematologic toxicities being the most common grade 3 or higher adverse events. All patients had cytokine release syndrome (CRS), which was grade 1 in 5 patients (50%) and grade 2 in 5 patients (50%). No neurotoxicity was observed after CAR‐T cell infusion. The overall response rate was 100%, with the best response being 90% for a stringent complete response (sCR), and 10% for a complete response (CR). At a median follow‐up of 42 (36–49) months, seven (70%) of 10 patients showed sustained minimal residual disease (MRD) negativity for more than 2 years. The median progression‐free survival (PFS) and overall survival (OS) were not reached. Although the sample size was small and there was a lack of control in this single‐arm study, the clinical benefits observed warrant ongoing randomized controlled trials.